2019
DOI: 10.3892/ijmm.2019.4408
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic SKOV3 cells stimulate M0 macrophages to differentiate into M2 macrophages and promote the�proliferation and migration of ovarian cancer�cells by activating the ERK signaling pathway

Abstract: Ovarian cancer has a high rate of recurrence, with M2 macrophages having been found to be involved in its progression and metastasis. To examine the relationship between macrophages and ovarian cancer in the present study, M0 macrophages were stimulated with apoptotic SKOV3 cells and it was found that these macrophages promoted tumor proliferation and migration. Subsequently, the mRNAs and proteins expressed at high levels in these M2 macrophages were examined by RNA-Seq and quantitative proteomics, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…The medium was renewed in half every 3 days and then supplemented with 100 ng/mL M-CSF. Cultivated to the 7-8th day, part of cells were harvested, and macrophage surface markers CD68 [16], CD163 [17], and CD206 [18] were tested by immunofluorescence assay [19] to identify macrophages.…”
Section: Induction Of Macrophagesmentioning
confidence: 99%
“…The medium was renewed in half every 3 days and then supplemented with 100 ng/mL M-CSF. Cultivated to the 7-8th day, part of cells were harvested, and macrophage surface markers CD68 [16], CD163 [17], and CD206 [18] were tested by immunofluorescence assay [19] to identify macrophages.…”
Section: Induction Of Macrophagesmentioning
confidence: 99%
“…In ovarian cancer and glioblastoma, transcriptomic profiling demonstrated that M0 macrophages do not fit into the canonical M1 or M2 model, but M0 macrophages did have high expression of M2 markers, and a transcriptional profile more similar to M2 macropha ges [47,48]. Ultimately, M0s…”
Section: Discussionmentioning
confidence: 99%
“…may represent another type of TAM or an incompletely differentiated M2 [47]. M0 macrophages were found to be one of the cell subsets most strongly associated with poor outcome in breast cancer [49], prostate cancer [50], and lung adenocarcinoma [51], while reduced M0 content has been associated with better prognosis in bladder cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…In liver cancer, M2-type macrophages could promote the malignant transformation and progression of liver cancer, through the induction of expression of vascular endothelial factors and matrix metalloproteins in the TME in comparison with M1-type macrophages, and facilitate the invasion and metastasis of liver cancer, which are important factors for poor prognosis of patients with liver cancer [33]. The tumor-supporting functions of TAMs have been demonstrated for in many types of malignancies including ovarian cancer, nasopharyngeal cancer, and melanoma, TAM was dominated mostly by M2-type macrophages; however, the reprogramming of M2 macrophages towards M1 phenotype exhibited a marked negative impact on tumor progression and prognosis [7,38,39]. These pieces of evidence thus indicated that M1-type macrophages present an inhibitory effect on tumor immunity, while M2-type macrophages exhibit a tumor-supporting function including tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%